Chemical constituents from stem bark of Garcinia prainiana and their bioactivities - On, Shamsul; Aminudin, Nurul Iman; Ahmad, Farediah; Mohd Sirat, Hasnah; Bakhtiar, M. Taher (International Journal of Pharmacognosy and Phytochemical Resear, 2016)
Phytochemical investigations on the hexane and methanol extracts of the dried stem barks of Garcinia prainiana resulted in the isolation of two triterpenes; 3β-hydroxyeupha-5,22-diene (1), 3β-acetoxyeupha-5,22-diene (2) as well as five flavonoids, morelloflavone (3), O-methylfukugetin (4), volkensiflavone (5), amentoflavone (6) and 4′′′- methoxyamentoflavone (7). Except for (3) and (5), the rest of the isolated compounds are reported here for the first time from this plant. The structures were established based on spectral analyses. The crudes and compounds were screened for DPPH radical scavenging assay and tyrosinase inhibition activity. The methanol extract and compound (3) were found to show high radical scavenging activity with IC50 15.1 and 15.7 g/mL, respectively. As for tyrosinase inhibition assay, compound (3) was found to exhibit the highest activity with IC50 34.0 mcg/mL